MANAGEMENT OF STRESS RELATED PSORIASIS W. S. R. TO CHETAH SAMAVAYI - Seetarama D, *Kishore; Puripanda, S Kamalakar; Shobhitha, Madhur; TB, Tripathy; Gazala, Hussain; kumar B, Anil (International Journal of Ayurveda and Pharma Research, 2016)
There is a wide range of importance for appearance in present era. Psoriasis is chronic disorder which is commonly encountered in day to days clinical practices. It is one of the burning issue having social importance. Increased stress and life style are main predisposing factor which is accounting for wide spared prevalence of this disease. Usually10-15% cases present before general practitioners are pertaining to skin diseases. Due to altered life style, lack of physical exercise, unhygienic, mental stress, over eating, skin diseases are commonly observed. We can observe many diseases popping up especially due to mental stress i.e., Manasa Vikriti. There is Samavaya Sambandha between Tvacha and Manas (Chetah Samavayi). Most of the Tvak Vikaras are psychologically agonising and have negative impact on quality of life. Here it is important to remember the citation of Acharya Charaka regarding the relationship between the Tvacha and Manas, Tvacha is considered as Chetah Samvayi i.e., the skin has an eternal relationship with Manas (psyche/mind). The knowledge of Nidana is helpful for the proper diagnosis, prevention of disease and treatment also. Thus to treat any Tvak Gata Vikara, Bhishak should consider the skin ailment as well as condition of Manas. This paper highlights a case study of stress related Kitibha Kusta (Psoriasis) treated with Shodhana Chikitsa.